العوامل المؤثرة في تخفیف الأعباء المنزلیة لدى المرأة العراقیة العاملة (Journal of the College of Education for Women, 2019)
In the past, an absolute authority was held by the father and his decisions were imposedand obeyed strictly without discussion. Later, many economical changes took place andaffected all of the family members dramatically creating a whole new concept of authorityin the family, a one that is based upon sound leadership, mutual understanding andconsultation among family members.Women carried responsibility of doing all domestic jobs and served family members,however, when she went to work outside her house, these loads began disturbing andexhausting her. Therefore, man started to participate in assisting his wife. In addition,industrial advances contributed in making these jobs easier than before.This has led the researcher to ask if the Iraqi husband did participate in helping his wifeand to what extent women depend upon different household electric devices on a dailybasis.The study sample was made of 150 ladies who were employees in different Iraqigovernmental facilities, high school teachers and faculty members. They were selectedonly if they were married and have children of 12 years of age or younger.The present study aims at identifying:1. Extent to which Iraqi men assist their wives in household loads.2. Extent to which Iraqi women benefit from domestic devices to minimize burdens ofdoing household jobs manually.3. Extent to which Iraqi women depend upon previously prepared foods purchased fromthe market.4. Extent to which Iraqi women admit being exhausted from domestic jobs.The most important result of the study show:1. About two thirds of study sample admit that their husbands help them in householdjobs. The majority of those husbands help their wives only occasionally and a smallpercentage always assist their wives.2. All the women in the present study bought previously prepared foods either on a dailybasis or only on occasions.3. In the present study, all the participants depended upon different household electrics tolower domestic loads.4. The majority of the study group feel exhausted from household jobs, however, onlyoccasionally. Only a small percentage doesn't feel consumed especially when theirhusbands share their loads.The researcher had made a number of recommendations including:Educational programs should include the subject of family support between a man andhis wife in household jobs (especially in boys' schools).Further studies could be conducted to know women's suggestions in minimizing householdburdens.